Fluorogenic l-alanylaminopeptidase substrates derived from 6-amino-2-hetarylquinolines and 7-amino-3-hetarylcoumarins and their potential applications in diagnostic microbiology. Issue 10 (15th May 2019) - Cellier-Rastit, Marie; James, Arthur L.; Orenga, Sylvain; Perry, John D.; Robinson, Shaun N.; Turnbull, Graeme; Stanforth, Stephen P.
Graphical abstract: Abstract: Six novel fluorogenic enzyme substrates for detecting l -alanylaminopeptidase activity in microorganisms have been prepared and evaluated in Columbia agar media. The substrates are l -alanyl derivatives of 6-amino-2-hetarylquinolines and 7-amino-3-hetarylcoumarins. Both the quinoline and coumarin series of substrates produced fluorescence in the presence of Gram-negative microorganisms. In contrast, fluorescence generation in the presence of the Gram-positive microorganisms and yeasts was limited or absent.